A report on the current access to academic information at the University of Pretoria for visually impaired students: challenges and opportunities. (3rd July 2018) - Cassells, Laetitia; Weber, Caitlin
ABSTRACT: This study aimed to determine what the best practice guidelines were for making academic reading material available to visually impaired students at the University of Pretoria (UP) easily and efficiently. A basic literature review of relevant research data was done to help create further context for this study. A semi-structured interview with a staff member from the Disability Unit at the UP as well as a focus group consisting of five visually impaired students who make use of the unit were used to obtain responses to the research questions. The visually impaired students felt that local publishers and UP staff needed further insight into these students' academic needs in order to make the acquisition process for their academic material run smoother and more efficiently.